FATTY ACID AND TRANSCRIPT PROFILING IN DEVELOPING SEEDS OF THREE BRASSICA NAPUS CULTIVARS - Petkova, Mariana; Chao, Wun S.; Cook, Leonard; West, Mark; Rahman, Mukhlesur; Foley, Michael E. (Plant Breeding and Seed Science, 2020)
Fatty acid levels and gene expression profiles for selected genes associated with the synthesis of fatty acids (FA), triacylglycerol, and oil body proteins were examined in three oilseed rape (Brassica napus) cultivars that have utility for cultivar development in our spring canola breeding program. The seed oil content of Bronowski, Q2, and Westar was 39.0, 40.1, and 40.6%, respectively at 40 days after flowering (DAF). During the 20 to 40 day period of seed development, cultivars had varying levels of palmitic, stearic, oleic, linoleic, α-linolenic, eicosenoic, and erucic acid. In general, the percentage of each FA was similar among the cultivars during seed development. However, the level of oleic acid was lower and the levels of eicosenoic acid and erucic acid were higher in Bronowski than in Q2 and Westar seeds; linoleic acid also tended to be lower in Bronowski. Gene expression among the cultivars was similar from 10 to 40 DAF. The few exceptions were that expression of KAS1 and SAD were higher in Westar and Q2 than in Bronowski at 25 DAF, SAD was highest in Q2, intermediate in Westar, and lowest in Bronowski at 35 DAF, FAD2 was higher in Q2 than in Bronowski at 35 DAF, FAD3 was higher in Q2 than in Bronowski at 15 DAF and Q2 and Westar at 25 and 30 DAF, and FAE1 was higher in Westar and Q2 than in Bronowski at 30 DAF. Correlation analysis for gene expression against DAF for each genotype supported a common trend in gene expression among the three cultivars with gene expression tending to decrease over time; except for LPAAT, which tended to increase. The correlation between the level of FAs and expression of genes by genotype indicated no general trend; rather correlations seem to depend on the genotype.